A PILOT STUDY ON THE EFFICACY OF AN INDIGENOUS ANTICANCER FORMULATION (AC COMPOUND) IN PATIENTS OF CANCER - Radheyshyam Sharma; Anamika Soni (Journal of Biomedical and Pharmaceutical Research, 2020)
Cancer is second to coronary artery disease as being the commonest cause of death in the western world. In India, as many as 2,500 persons die every day due to tobacco-related diseases. One woman dies of cervical cancer every 8 minutes in India. In Modern medicine, the available treatment modalities viz chemotherapy and radiotherapy cause decrease in immunity, decreased Quality of life, poor tolerance to surgery and altered efficacy of Chemotherapy and Radiotherapy. Ancient Ayurveda classics have described about tumours as ‘Arbuda’. Ayurveda can be helpful in the management of cancer in many ways- as prophylactic, palliative, curative or supportive therapy. No doubt, it helps to improve quality of life (QOL) as adjuvant or as co therapy along with chemotherapy or radio therapy & Post surgery care. Ayurvedic drugs also minimize the side effects of Chemo/radio and other therapies. So, the current pilot study was done with the motive to evaluate the effect of a hypothetical compound (AC Compound) in the patients of Cancer. A significant improvement in some of subjective parameters like general well being, pain, indigestion, constipation and headache was seen in patients as a result of therapy. The results obtained from trial encourage more exploration and extended clinical trials in this field. Keywords: Immunity, Chemotherapy, Radiotherapy, Arbuda, AC compound